MtCOI DNA sequences from Sycanus aurantiacus (Hemiptera: Heteroptera: Reduviidae) provide evidence of a possible new harpactorine species from Bali, Indonesia - I Putu Sudiarta; Dewa Gede Wiryangga Selangga; Gusti Ngurah Alit Susanta Wirya; Ketut Ayu Yuliadhi; I Wayan Susila; Ketut Sumiartha (Jurnal Entomologi Indonesia, 2021)
Sycanus aurantiacus Ishikawa & Okajima, found in Bali, was first described in 2007 as a new harpactorine species based on morphological and biological characteristics; however, its genome has not yet been sequenced. In this study, we examine the mitochondrial cytochrome oxidase subunit I (MtCOI) nucleotide sequence of S. aurantiacus in order to determine whether it represents a new harpactorine species. A sample from Pancasari, Bali, Indonesia was collected at the same location S. aurantiacus was first discovered in 2007. The selected mtCOI gene (650 bp) was successfully amplified using mtCOI primer pairs LCO1490 and HCO2198, and the resulting MtCOI sequence of the S. aurantiacus sample was compared with those from other hapactorine species recorded in GenBank. This comparison revealed low genetic similarity between S. aurantiacus and most other harpactorine species worldwide, except for the Genus Sycanus (JQ888697) from USA whose mtCOI shares approximately 91% similarity with the Pancasari sample. Phylogenetic analysis indicated a close genetic relationship between Sycanus from Bali and the Genus Sycanus (JQ888697) from the USA. The mtCOI sequence of S. aurantiacus had not been recorded previously, and our comparison with existing Sycanus sequences provides support to the understanding that S. aurantiacus is indeed its own species.